Longman academic reading series. 4 : reading skills for college / Robert F Cohen, Judy L Miller - Cohen, Robert F.
"The Longman Academic Reading Series is a five-level series that prepares English language learners for academic work. The aim of the series is to make students more effective and confident readers by providing high-interest readings on academic subjects and by teaching them skills and strategies for effective reading, vocabulary building, note-taking, and critical thinking. The series also encourages students to discuss and write about the ideas they discovered in the readings, making them better speakers and writers of English as well."--Publisher description.